Empirical evidence of the relationship between regulatory efficiency, market openness, and bank productivity in economies at different income levels: evidence from selected Asian and MENA countries - Kamarudin, Fakarudin; Hussain, Hafezali Iqbal; Mohamad Anwar, Nazratul Aina; Michałek, Janusz; Ahmad Razimi, Mohd Shahril (Institute of Economic Research, 2024)
Research background:Economic freedom plays a pivotal role in ensuring the progressive productivity of banks. It fosters a favorable economic climate and acts as a catalyst for the generation of innovative ideas. In addition, economic freedom allows new domestic and foreign entrants in the banking sector which leads to increased competition as well as wider range of product offerings and thus potentially affect bank efficiency. Purpose of the article: This study aims to identify the effects of regulatory efficiency and market openness in terms of economic freedom on the bank’s productivity at three income levels: lower-middle, upper-middle, and high-income economies. Methods: A sample of 15 countries are included in the study from differing income levels. The study uses the data envelopment analysis (DEA) based Malmquist productivity index (MPI) approach to measure banks’ productivity. This non-parametric approach measures the relative efficiency of banks by considering the production change while taking into account technical efficiency change and technological change in order to capture a comprehensive view over time. Then, regression analysis was performed utilizing the ordinary least squares (OLS) approach, fixed effect (FE), and random effect (RE) panel multiple regression estimation methods are utilized to measure economic freedoms and other determinants’ effect on banks’ productivity change over time. Findings & value added: The results show that banks in high-income economies are more productive and have higher growth rates than those in upper-and lower-income economies. Furthermore, starting, obtaining permits, and closing businesses under business freedom have a detrimental effect on banks’ output, whereas the effects of labor freedom on employing, managing, and supervising staff members have a substantial favorable impact on banks’ productivity. Moreover, financial freedom and investment freedom under the market openness dimension negatively influence banks’ productivity. Government intervention is required to introduce regulations that allow foreign countries to provide labor at lower wages, introduce tax allowances, and control inflation rates. Thus, the empirical results of this study will benefit regulators and policymakers in developing a system and plan to increase banks’ productivity based on indicators of business, labor, financial, and investment freedom.